2022
DOI: 10.5713/ab.22.0014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feeding high-energy diet on growth performance, blood parameters, and carcass traits in Hanwoo steers

Abstract: Objective: Our study aimed to investigate the effects of a 2% increase in dietary total digestible nutrients (TDN) value during the growing (7 to 12 mo of age) and fattening (13 to 30 mo of age) period of Hanwoo steers.Methods: Two hundred and twenty Hanwoo steers were assigned to one of two treatments: i) a control group (basal TDN, BTDN, n = 111 steers, growing = 70.5%, early fattening = 71.0%, late fattening = 74.0%) or high TDN (HTDN, n = 109 steers, growing = 72.6%, early = 73.1%, late = 76.2%). Growth pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
5
9
0
Order By: Relevance
“… May et al (1992) also found that sensory tenderness scores decreased (p<0.05) for steaks from steers with a mean back-fat thickness of 21.08 mm. Previous study suggested that the carcass maturity ( Jerez-Timaure et al, 2013 ) and age could affect tenderness ( Kang et al, 2022 ). Maturity and age were kept similar for all the animals in our study.…”
Section: Resultsmentioning
confidence: 99%
“… May et al (1992) also found that sensory tenderness scores decreased (p<0.05) for steaks from steers with a mean back-fat thickness of 21.08 mm. Previous study suggested that the carcass maturity ( Jerez-Timaure et al, 2013 ) and age could affect tenderness ( Kang et al, 2022 ). Maturity and age were kept similar for all the animals in our study.…”
Section: Resultsmentioning
confidence: 99%
“…Ku et al [ 39 ] found no significant effect of different forage proportions in TMR on meat color of Hanwoo sirloins. In contrast, Kang et al [ 40 ] found a significant increase in a* and a trend toward an increase in L* and b* in the longissimus dorsi (LD) muscle of Hanwoo steers fed high-energy diets compared with the group fed a basal diet. The explanation for the improvement in meat color by feeding a high-energy diet could be influenced by muscle metabolism, intramuscular fat, and muscle fiber properties [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 96%
“…The explanation for the improvement in meat color by feeding a high-energy diet could be influenced by muscle metabolism, intramuscular fat, and muscle fiber properties [ 40 , 41 ]. In the current study, meat color was not affected by energy intake, possibly due to differences in breed, feeding, timing of meat color measurement, or sampling, because color in the current study was measured on chilled meat two days post-mortem, whereas in Kang et al [ 40 ] it was measured after thawing of muscle samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Providing propionate for glucose synthesis via gluconeogenesis may also contribute to triglycerol synthesis. Therefore, large proportions of concentrates or grain are routinely included in the diet when fattening beef cattle [66][67][68][69]. Supplementing the finishing diet with 100 ppm γ-aminobutyric acid was found to improve antioxidant enzyme status in the longissimus lumborum of Korean cattle steers [70].…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%